Nanoscratch on single-layer MoS2 crystal by atomic force microscopy: semi-circular to periodical zigzag cracks. (28th November 2018) - Ye, Shili; Xu, Kunqi; Lei, Le; Hussain, Sabir; Pang, Fei; Liu, Xinmeng; Zheng, Zhiyue; Ji, Wei; Shi, Xinghua; Xu, Rui; Xie, Liming; Cheng, Zhihai
Abstract: The fracture behaviors of single-layer molybdenum disulfide (MoS2 ) grown on SiO2 /Si wafer by chemical vapor deposition (CVD) were systematically investigated here via a technique that combining AFM-based nanoscratch tests with friction force microscopy (FFM). To get a complete cognition of fracture behavior and deepen the understanding of different fracture stages in the process, nanoacratch with progressive and constant force was done step by step. The radius of AFM tip we used is ∼10 nm which is relatively blunt to produce a tensile fracture rather than pierce the film at the initial stage. As a result, there were novel crack modes with specific normal load in the surface of CVD-grown MoS2 : semi-circular and periodical zigzag cracks, and both crack modes exhibit anisotropy during the generation and propagation. The scratch study of single-layer MoS2 film has exhibited the gradual process of fracture behavior on nanoscale layered films and confirmed the mesoscopic anisotropy of the mechanical failure of 2D materials.